Langkah-Langkah Pengembangan Bahan Ajar PAI - Srihartini, Yusi; Rihma, Wildya Agna; Wahyudi, Titono (Al-Wasathiyah: Journal of Islamic Studies, 2024)
Learning resources are basically teaching materials used in the learning and learning process that aims to facilitate the objectives and learning process takes place. Interactive multimedia is a learning material that utilizes technological advances and is used to channel learning messages in the form of knowledge, skills and attitudes that can stimulate mindset, attention, The willingness and feelings of students in the learning process so that intentionally the learning process can occur, be controlled, and purposeful and can affect learning outcomes. Research steps that can be used in multimedia development are using the multimedia development model by Lee & Owen where there are 5 steps, namely analysis, design, development, implementation, and evaluation. These steps can later conclude that the developed media is not worth using.